The role of taekwondo training on the subjective wellbeing of adolescents in Addis Ababa, Ethiopia (Revista de Artes Marciales Asiáticas, 2015)
The purpose of this study was to investigate the role of taekwondo (TKD) training on the subjective well-being (SWB) of adolescents (12-18 years old) in Addis Ababa city. A cross-sectional survey method was used; self-administered questionnaire was the main data collection tool. A total number of 162 adolescents (108 TKD adolescents from four randomly selected TKD clubs and 54 non-TKD adolescents from a randomly selected public high school), participated in the study. The study sought to determine TKD adolescents’ level of SWB as measured by the Personal Wellbeing Index – School Children (PWI-SC). Besides, adolescents in different groups (TKD adolescents in three groups according to rank/belt level and TKD adolescents and non-TKD adolescents) were compared based on their score of PWI-SC. Results of the study showed that: (1) TKD adolescents had high level (mean points) of SWB as measured by the PWI-SC, i.e., 81.95 (95%CI: 79.70 to 84.20); (2) there was no significant difference in SWB among the three groups of TKD adolescents (lower, middle and high level belts) (F(2, 81) = 1.58, p > .05.); and (3) when compared with non-TKD adolescents, TKD adolescents were found to have a significantly higher mean points of SWB, (t = 4.25(77.97), p < 0.001; d = 0.79). Overall, the results of this study indicated the training of TKD can have a positive contribution to adolescents’ well-being.